2017
DOI: 10.1007/s11136-017-1678-2
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in Spanish informal caregivers: gender differences and support received

Abstract: Male and female caregivers in Spain differ in received support and how their HRQoL is affected. These differences are important to design interventions to promote more equitable sharing of care responsibilities and better caregiver health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 26 publications
8
46
0
1
Order By: Relevance
“…Other findings reported in the present study are consistent with previous research; we also found that caregivers had a poorer HRQoL than non-caregivers [10][11][12]22,32,33] and experience more pain/discomfort and anger/hostility [37]. This may be due to their daily caring tasks, the functional disabilities of the patients, and the duties involved in patient supervision [38].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Other findings reported in the present study are consistent with previous research; we also found that caregivers had a poorer HRQoL than non-caregivers [10][11][12]22,32,33] and experience more pain/discomfort and anger/hostility [37]. This may be due to their daily caring tasks, the functional disabilities of the patients, and the duties involved in patient supervision [38].…”
Section: Discussionsupporting
confidence: 91%
“…According to recent research, symptoms such as hostility, obsessive-compulsive, and paranoid ideation, among others, have been somewhat documented in studies of spousal caregivers [34][35][36], but this psychological symptomatology is less reported in other populations who do not have the responsibility of looking after their relatives every day. For this reason, our study also compared these psychological symptoms between caregivers and non-caregivers, finding that caregivers reported higher levels of general distress than matched controls [32]. This symptomatology could be derived from patient behaviour problems, social desirability, or the need to provide increasing levels of daily living assistance [20,34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations